Rhoicosphenia kloseri, a new isopolar Rhoicosphenia (Bacillariophyta) species from the Antarctic with comparison to other isopolar Rhoicosphenia - Thomas, Evan W.; Ligowski, Ryszard (Phytotaxa, 2016)
Rhoicosphenia is a common diatom in both freshwater and marine ecosystems and the genus can be found on nearly every continent. Despite the fact that the genus is common, few new species have been reported from outside of Europe, Asia, and North America, and only one species has been previously described from the Antarctic. Further, most Rhoicosphenia are heteropolar in valve outline, asymmetrical to the transapical axis, while few taxa are isopolar. During investigations into the epiphytes on the red alga Georgiella confluens from the South Shetland Islands, a new marine, isopolar Rhoicosphenia was discovered and is herein described and documented with both light and scanning electron microscopy. Rhoicosphenia kloseri is isopolar, and in that regard similar to other isopolar taxa, such as R. genuflexa and R. pullus, but does not fit the morphological species concept of those taxa and is thus described as new. This new species discovery is following a trend of high rates of discovery of previously ignored morphological diversity within the genus Rhoicosphenia.